The Efforts of Housewife to Improve Communication Patterns in the Family at Padang Lawas Regency, North Sumatera - Sudirman Sudirman; Inayati Hasni Nasution; Rosramadhana Rosramadhana (BIRCU, 2020)
The problem in this study is communication within the family, specifically between fathers and young women who are not well- established. The role of mothers who tend to be considered not to facilitate the occurrence of good communication patterns between fathers and young women in the family. This study aims to describe information about the pattern of communication that exists between fathers and young women in the family, then describe the role of mothers as communication facilitators in family and to find out the results of communication patterns between fathers and young women. The theory used about